P353 Aberrant brain structural large-scale connectome in Crohn's disease. (25th January 2019) - Thomann, A; Griebe, M; Ebert, M; Thomann, P; Reindl, W
Abstract: Background: Altered brain-gut-interactions and a bidirectional relationship between inflammation and psychiatric symptoms such as anxiety and depression are being discussed in patients with inflammatory bowel diseases (IBD). Alterations of brain structure and function in IBD have been reported by previous magnetic resonance imaging (MRI) studies with heterogeneous and partly conflicting results, hindering the establishment of a „neural phenotype' of IBD. Whether brain structural changes reflect independent localised deficits or rather a systematic disruption in the anatomical organisation of large-scale brain networks remains unclear. The present study therefore investigated the gray matter structural connectome in patients with Crohn's disease (CD). Methods: Sixty participants (30 with quiescent CD and 30 matched healthy controls (HC)) underwent high-resolution brain MRI at 3 Tesla. Using graph theoretical analysis, well-established graph metrics were analysed at the global and regional network level and compared between groups. Results: The networks in both groups followed a small-world organisation, i.e. an architecture that is simultaneously highly segregated and integrated. However, transitivity (a measure of global network segregation) was significantly reduced in patients with CD (p = 0.003) Regionally, CD patients showed reduced nodal betweenness centrality (a measure of information flow) in the right insula and cuneus and the left superior frontal cortex as well as reduced nodal degree within the left-hemispheric cingulum and the left lateral and right medial orbitofrontal cortex Conclusions: These findings advance our understanding of aberrant brain morphology in CD and lend support to the hypothesis that the disorder is accompanied by alterations in both global network organisation and regional connectivity. Future studies should investigate these factors in different disease states to determine the influence of inflammation on neural networks and shed light on possible neural correlates of disrupted brain-gut-interactions in IBD. A deeper understanding of neural networks in IBD may eventually help to develop complementary strategies in the personalised treatment of patients with 'extraintestinal' issues like anxiety, depression, or maladaptive coping.